Predicting COVID-19 outbreaks by measuring SARS-CoV-2 RNA in sewage sludge - Peccia, Jordan (Henry Stewart Talks, 2020)
Measuring viral RNA in sewage water: methods and insights, Reliability of measuring SARS-CoV-2 RNA in sludge, Estimation of time lag between appearance of viral RNA in sewage water and start of outbreak, Implications of introducing public health measures, Increased efficiency of public health responses using viral RNA in sewage water